Outbreaks of foodborne Salmonella enteritidis in the United States between 1990 and 2015: An analysis of epidemiological and spatial-temporal trends. (April 2021) - Sher, Azam Ali; Mustafa, Bahar E.; Grady, Sue C.; Gardiner, Joseph C.; Saeed, A. Mahdi
Highlights: Food items based on meat, vegetables, and eggs, are responsible for outbreaks of Salmonella enteritidis (SE) in the USA. Special food regulations and precautions should be implemented to prevent foodborne SE infections during the summer season. In addition to restaurants, there is a timely need to educate the public with regards to the reduction of SE infections in homes or private residences. Active disease surveillance should be enhanced to mitigate the increasing burden of SE infections in the USA. Abstract: Objectives: To evaluate the role of eggs and other food vehicles as risk factors associated with Salmonella enteritidis (SE) outbreaks in order to address the endemicity of SE infections in the USA. Methods: We retrieved and analyzed data relating to all SE outbreaks reported to the Centers for Disease Control and Prevention (CDC) between 1990 and 2015. We then used descriptive and analytical statistical methods, including negative binomial regression models for the estimation of rate-ratios, to analyze the data. Results: Analyses showed that egg-based dishes were the most common food vehicle associated with outbreaks of SE in the USA (273 cases [24%]); this was followed by several other food items, including meat (130 cases [11%]), vegetables (96 cases [8%]), chicken items (95 cases [8%]), dairy products (55 cases [5%]), and bakery items (8 cases [1%]). Compared to egg-based dishes, other food items such as meat (exp(β) = 0.51, 95% CI 0.37, 0.69), chicken (exp(β) = 0.42, 95% CI 0.30, 0.58), vegetables (exp(β) = 0.41, 95% CI 0.29, 0.55), and dairy items (exp(β) = 0.27, 95% CI 0.18, 0.40) were significantly associated with outbreaks of SE in the USA. Of 1144 SE outbreaks, 402 (35%) occurred in the Northeast region of the USA, followed by the South (253 [22%]), West (250 [22%]), and Midwestern regions (239 [21%]). Conclusions: Epidemiological and spatiotemporal trends analyses demonstrated that a significant proportions of Salmonella enteritidis outbreaks in the USA are attributed to food vehicles other than eggs. Our findings can be used to plan effective strategies to mitigate the increasing occurrence of foodborne SE outbreaks.